Participatory irrigation management - Oke, Adebayo; Atengdem, P. B.; Zemadim, Birhanu; Cofie, Olufunke O. (International Water Management Institute, 2025)
Participatory Irrigation Management (PIM) involves farmers and stakeholders in managing irrigation systems, shifting from centralized control to local ownership. It aims to enhance water use efficiency, equity, and system sustainability. By engaging farmers in planning, operation, and maintenance, PIM ensures better water allocation, reduces wastage, and boosts agricultural productivity. This approach fosters responsibility among users, leading to improved livelihoods and a sustainable, equitable irrigation system that benefits both farmers and the environment. This fact sheet elaborates on the process of participatory irrigation management.